Analisis Pengaruh Brand Equity terhadap Finalisasi Pembelian di Industri Marketplace (Studi pada Pelanggan X) - Eka Nurul Indah Wulansari; Mohamad Ilyas Ichsanuddin; Nesa Tri Andini; Intan Luqyana (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The increasingly fierce competition in the marketplace industry demands that every brand has strong Brand Equity to attract attention and encourage consumers to complete the purchase process. Brand Equity itself is a combination of several important elements, namely Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty. These four variables are believed to have an important role in shaping consumer perceptions and influencing their final decision to complete transactions on the marketplace platform. This study aims to measure the extent to which the four dimensions of Brand Equity influence the finalization of purchases by customer X. The method used is a descriptive quantitative approach, involving 39 respondents who have made transactions through platform X. Data were obtained through the distribution of online questionnaires and then analyzed using multiple linear regression with the help of SPSS software. The results of the study show that all variables, namely Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty, are proven to have a positive and significant influence on purchase finalization. This means that the higher the level of consumer awareness of a brand, the stronger the association they build, the better the perceived quality, and the higher the customer loyalty, the greater the likelihood of consumers completing the purchase process. These findings have strategic implications for businesses in the marketplace sector. Building a consistent brand image, maintaining product and service quality, and cultivating sustainable relationships with consumers are crucial for maintaining competitiveness. Furthermore, businesses need to utilize appropriate digital marketing strategies to enhance customer experience and strengthen emotional ties with the brand. Therefore, solid brand equity can be a key foundation for business sustainability amidst increasingly dynamic competition.